EXPLORATORY STUDY FOR REGRESSION TEST SELECTION TECHNIQUES IN PROCEDURAL AND OBJECT ORIENTED PROGRAMMING PARADIGM (International Journal of Engineering and Computer Science, 2014)
The most crucial phase in the software development life cycle is maintenance phase. Whether it is corrective, adaptive or perfective maintenance it must be ensured that the modification does not affect other portions of the program. Therefore testing is required. Regression testing is carried out after a software developer has attempted to fix a problem or has introduced source code to software. An important research problem in regression testing is the selection of a suitable subset of test cases from existing test suite that would reduce the regression testing time and effort without giving up the completeness of regression testing. Researchers have suggested a number of regression test selection (RTS) techniques for different programming paradigms. In this paper an exploratory study of regression test selection techniques was carried out for procedural and object-oriented programming paradigm. From the study it was concluded that Specification Based RTS Technique is most effective as it does not depend on model-based or code based analysis.